Impact and effects of the patient-centered approach in diabetic patients: A neuro-educational approach adapted to the concepts of empowerment and reflexivity - Essellouti, Jamila; Bassiri, Mustapha; Tridane, Malika; Belaaouad, Said (Edelweiss Applied Science and Technology, 2024)
This study aims to assess the impact and effects of PCA on diabetic patients within a neuro-educational framework that aligns with the concepts of empowerment and reflexivity, demonstrating its influence on patient satisfaction and the development of cognitive and behavioral skills. Conceptually, the patient-centered approach (PCA) offers the possibility of implementing a neuro-educational approach for diabetic patients (WHO). However, the key question is its practical application in general practice. A neuro-educational approach to PCA was tested on a sample of 50 diabetic patients selected by 5 general practitioners. The aim was to adopt a comprehensive biopsychosocial approach, use global listening to understand patients' points of view, offer personalized advice, establish common ground on objectives, and identify the needs and obstacles affecting their management. We conducted a cross-sectional analysis to examine the processes involved in changing behavior and acquiring skills. The study revealed a significant positive response, as well as the acquisition of reflexivity and autonomy skills in the majority of diabetes patients. Some patients showed a significant improvement in their sense of self-efficacy. However, a minority expressed resistance to this new support strategy. Ultimately, the educational approach within the PCA enabled diabetic patients to adapt and modify their behaviour, thus contributing to the acquisition of valuable skills. At the end of this study, PCA, enriched by other psychotherapeutic approaches, emerged as a systemic therapeutic support process that could be accessible to all general practitioners, teachable, and the subject of further research.